A linkedin content plan for a cleantech startup Annea, Portugal - Sultanova, Dana (2022)
The Covid-19 pandemic impacted the B2B market significantly, transferring numerous in-person meetings and conferences into the digital space. However, this new reality can be really beneficial for agile startups and small companies, as they can decrease the high travel costs and can be creative and proactive on social media instead. LinkedIn, being the most recognised platform for B2B lead capturing, has become a B2B content sharing platform as well. This in-company project is carried out in collaboration with the German cleantech startup ANNEA. The purpose of this work is to develop a LinkedIn content plan and analyse its efficiency. In this project the inbound marketing concept was introduced. It was used as a theoretical underpin for B2B content creation. LinkedIn Sales Navigator was used as an instrument to support a so-called social listening approach, which is a part of an inbound marketing concept. After the LinkedIn content plan for ANNEA was developed and implemented, the main LinkedIn metrics were gathered and analysed. The analysis shows that the engagement rate increased after the implementation of the described approach (by 60% from October 2020 to June 2021). However, other important metrics like Reactions and Clicks decreased, while Shares stayed at the same level. The best-performing topics were found and recommended for the further content creation. They include sustainability and green energy, as well as offshore wind energy development. It was also recommended to use more visuals in further posts and showcase more examples of green energy usage by households and individuals.